2009
DOI: 10.1016/j.jcf.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

High treatment burden in adults with cystic fibrosis: Challenges to disease self-management

Abstract: Background More aggressive management of cystic fibrosis (CF), along with the use of new therapies, has led to increasing survival. Thus, the recommended daily treatment regimens for most CF adults are complex and time consuming. Methods In the Project on Adult Care in CF (PAC-CF), an ongoing longitudinal study of CF adults, we assessed self-reported daily treatment activities and perceived treatment burden as measured by the CF Questionnaire-Revised (CFQ-R), a disease-specific quality of life measure. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
342
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(364 citation statements)
references
References 15 publications
13
342
3
6
Order By: Relevance
“…Patients with CF require numerous therapies to manage these symptoms (3), including mucolytic and antibiotic agents and chest physiotherapy to treat the airway disease and digestive enzymes to replace the loss of exocrine pancreatic function. These and other interventions have increased life expectancy dramatically, but improvement is needed to reduce the high treatment burden and increase survival (6,7).…”
mentioning
confidence: 99%
“…Patients with CF require numerous therapies to manage these symptoms (3), including mucolytic and antibiotic agents and chest physiotherapy to treat the airway disease and digestive enzymes to replace the loss of exocrine pancreatic function. These and other interventions have increased life expectancy dramatically, but improvement is needed to reduce the high treatment burden and increase survival (6,7).…”
mentioning
confidence: 99%
“…High-frequency chest wall oscillation is used by 37% of people with CF in the USA [17], but only 3% in Canada [18] and 1% in the UK. Exercise is the most common airway clearance technique in New Zealand (46% of adults) [19], compared with 16% in the UK.…”
Section: Variation By Countrymentioning
confidence: 99%
“…This is evidenced by the low percentages of people with CF who reported that they did not use any airway clearance techniques: 10% in this UK study, 4% in the New Zealand data, 8% in the Canadian registry data and no other reports within the other data identified in this paper [16][17][18]20].…”
Section: Variation By Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…Factors related to disease severity, such as reduced lung function may restrict employment choices for adults with CF, and the treatment burden further compounds this; adults with CF are generally expected to perform physiotherapy regularly and there are the added demands of taking large numbers of therapies, including frequent visits to hospital (Sawicki et al 2009). …”
Section: Longitudinal Employment Status In People With Cfmentioning
confidence: 99%